Trends in Global Advertising and Cultures in Nigeria - Abubakar Sidiq Suleman; Bello Mukhtar Abiola (GREAT : Journal of Global Economic Trends, 2026)
Globalisation and digital media expansion have significantly transformed advertising practices across contemporary societies, increasing the circulation of transnational advertising messages and their influence on local cultural systems. This development has generated scholarly concern regarding the implications of global advertising for indigenous cultural values, identity formation, and cultural sustainability within Nigeria’s culturally diverse environment. This study examined the trends of global advertising and their influence on local cultures in Nigeria. Specifically, the study explored the nature of global advertising practices, the role of glocalisation and cultural adaptation, audience negotiation and resistance, regulatory interventions, and the implications of global advertising for cultural preservation in Nigeria. The study adopted a qualitative desk research design using a systematic literature review approach. Data were obtained from secondary sources, including peer-reviewed journal articles, books, policy documents, and credible academic publications related to advertising, globalisation, media culture and Nigerian communication practices. The collected data were analysed using thematic content analysis. The findings revealed that global advertising in Nigeria operates through a hybrid interaction between global standardisation and local cultural adaptation. Multinational advertisers increasingly integrate indigenous languages, Nigerian celebrities, Afrobeats music, and culturally familiar narratives into advertising campaigns. However, global advertising continues to promote consumerism, Western beauty ideals, materialistic lifestyles, and cosmopolitan aspirations that influence Nigerian cultural values and identity. The study also found that Nigerian audiences actively negotiate and reinterpret advertising messages, while regulatory institutions such as ARCON moderate culturally insensitive advertising practices. The study concludes that global advertising simultaneously functions as a mechanism of cultural influence, cultural negotiation, and cultural hybridity in Nigeria.